Medieval clothing and textiles, Volume 12 - Netherton, Robin 1959-; Owen-Crocker, Gale R. 1947- (The Boydell Press, 2016)
The studies collected here range through art, artifacts, documentary text, and poetry, addressing both real and symbolic functions of dress and textiles. John Block Friedman breaks new ground with his article on clothing for pets and other animals, while Grzegorz Pac compares depictions of sacred and royal female dress and evaluates attempts to link them together. Jonathan C. Cooper describes the clothing of scholars in Scotland's three pre-Reformation universities and the effects of the Reformation upon it. Camilla Luise Dahl examines references to women's garments in probates and what theyreveal about early modern fashions. Megan Cavell focuses on the treatment of textiles associated with the Holy of Holies in Old English biblical poetry. Frances Pritchard examines the iconography, heraldry, and inscriptions on a worn and repaired set of embroidered fifteenth-century orphreys to determine their origin. Finally, Thomas M. Izbicki summarizes evidence for the choice of white linen for the altar and the responsibilities of priests for keeping it clean and in good repair